2016
DOI: 10.1021/acs.biochem.6b00425
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of Carotenes and Xanthophylls in Photosystem I Photoprotection

Abstract: Carotenes and their oxygenated derivatives, xanthophylls, are structural elements of the photosynthetic apparatus and contribute to increasing both the light-harvesting and photoprotective capacity of the photosystems. β-Carotene is present in both the core complexes and light-harvesting system (LHCI) of Photosystem (PS) I, while xanthophylls lutein and violaxanthin bind exclusively to its antenna moiety; another xanthophyll, zeaxanthin, which protects chloroplasts against photooxidative damage, binds to the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 88 publications
0
46
0
1
Order By: Relevance
“…It is possible that by rapidly converting carotenoids into ketocarotenoids, photosystem assembly is hindered, and lower chlorophyll amounts accumulate in the algal cell. Another possible reason for the observed decrease of chlorophyll contents in cells expressing CrBKT could be that photosynthetic complexes, assembled without proper carotenoids, generate more ROS that damage photosynthetic membrane (Cazzaniga et al, 2016), however, this hypothesis is less probable as not perturbation in growth rates were observed. In addition, high-light intensities were tolerated by cells, and ketocarotenoids exhibit high antioxidant capacities which would likely protect membranes from ROS damage.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is possible that by rapidly converting carotenoids into ketocarotenoids, photosystem assembly is hindered, and lower chlorophyll amounts accumulate in the algal cell. Another possible reason for the observed decrease of chlorophyll contents in cells expressing CrBKT could be that photosynthetic complexes, assembled without proper carotenoids, generate more ROS that damage photosynthetic membrane (Cazzaniga et al, 2016), however, this hypothesis is less probable as not perturbation in growth rates were observed. In addition, high-light intensities were tolerated by cells, and ketocarotenoids exhibit high antioxidant capacities which would likely protect membranes from ROS damage.…”
Section: Discussionmentioning
confidence: 96%
“…The xanthophylls lutein, violaxanthin and neoxanthin are ligands for the photosystem antenna subunits, β-carotene is a ligand for both photosystem core complexes and antenna, while astaxanthin, in H. lacustris, is manly accumulated as a free form in the membrane, although it has been reported to bind photosystems (Mascia et al, 2017) . In a photosynthetic cell, the absence of carotenoids hinders photosystem assembly and reduces chlorophyll content (Cazzaniga et al, 2016). It is possible that by rapidly converting carotenoids into ketocarotenoids, photosystem assembly is hindered, and lower chlorophyll amounts accumulate in the algal cell.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that the concentration of O 2 required to induce PSI photoinhibition in the fluctuating‐light analysis and under rSP illumination is sufficiently higher than the O 2 concentration required for O 2 reduction in the thylakoid membrane. Recent studies have suggested that 1 O 2 is involved in PSI photoinhibition, although it was assumed that 1 O 2 is not generated in PSI (Hideg and Vass , Cazzaniga et al , , Takagi et al ). Under the highly reducing conditions of PSI, triplet‐state P700 ( 3 P700), which is a source of 1 O 2 production in PSI, is generated by the back reaction of P700 + and A 0 − from P700 + and A 1 − within PSI (Frank et al , Rutherford and Mullet , Setif et al , Ikegami et al , Sétif and Brettel , Polm and Brettel , Rutherford et al ).…”
Section: Discussionmentioning
confidence: 99%
“…P700 oxidation is expected to negate the effect of hydroxyl radicals by suppressing O 2 2 generation and by oxidizing the ironsulfur centers (Sonoike 1996). Recently, it was suggested that 1 O 2 triggers PSI photoinhibition (Cazzaniga et al, 2012(Cazzaniga et al, , 2016Takagi et al, 2016). Keeping P700 oxidized should help suppress 1 O 2 generation.…”
Section: Discussionmentioning
confidence: 99%